Influence of Pore Size on Ethylene Hydrate Formation in Carbon Materials - Wei, Yajuan; Sun, Yan; Su, Wei; Liu, Jia (adsorption science technology, 2014)
The formation of gas hydrates in porous carbon materials is highly dependent on the potential field in the pores. The formation of ethylene hydrate from water and ethylene in carbon materials with different pore-size distributions was investigated at 303 K. The potential field in the pores was favourable for the formation of gas hydrate when the pores were less than 1.2 nm. By comparison, when the pores were larger than 6 nm, little ethylene hydrate was formed. When the pore sizes were less than 2.35 nm, the ethylene molecules occupied both the large (L) and small (S) cavities simultaneously. However, when the pore sizes were greater than 2.82 nm, only the L cavities were occupied. This was proven by measuring the molar ratio of the water to ethylene at equilibrium. Chemistry, Applied Chemistry, Physical Engineering, Chemical SCI(E) EI 1 ARTICLE liujia@tju.edu.cn 9 717-724 32